2018
DOI: 10.1016/j.jams.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupressure on Preoperative Cesarean Section Anxiety

Abstract: Anxiety is a common preoperative problem in cesarean section candidates. Non-pharmacologic anxiety control has been demonstrated to be more suitable in pregnant women. The current study was a randomized, single-blind clinical trial which evaluated the effect of acupressure on preoperative C-section anxiety. In this study, 60 patients facing surgery were randomly divided into two groups of 30 patients each. Those patients in the intervention group received simultaneous acupressure at the Yintang and HE-7 acupoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
1
15
1
7
Order By: Relevance
“…Anxiety is a core manifestation of anxiety disorder, which is characterized by persistent fear and despair, and is accompanied by the development of physical symptoms such as tachycardia, tension, pain, and inability to relax. Several reviews and meta-analyses have proven the positive effect of acupuncture on reducing state anxiety [8][9][10][11]. To our knowledge, there have been no other meta-analyses of RCTs conducted concerning the effectiveness of acupuncture on anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety is a core manifestation of anxiety disorder, which is characterized by persistent fear and despair, and is accompanied by the development of physical symptoms such as tachycardia, tension, pain, and inability to relax. Several reviews and meta-analyses have proven the positive effect of acupuncture on reducing state anxiety [8][9][10][11]. To our knowledge, there have been no other meta-analyses of RCTs conducted concerning the effectiveness of acupuncture on anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that acupuncture has a positive effect on situational anxiety related to operations, dental treatment, and examinations [9][10][11][12]. There are also several reviews and meta-analyses that have shown that acupuncture has positive effects on state anxiety [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Akupresur aman pada semua populasi mulai dari anak-anak hingga lansia. Akupresur merupakan pilihan terapi yang tidak berbahaya dan tidak memiliki efek samping karena bersifat non -invasif, dapat dilakukan oleh individu itu sendiri tetapi memerlukan pelatihan khusus dan hemat biaya (Abadi et al, 2018;Hmwe et al, 2015;Lane, 2009). Akupresur memiliki efek menenangkan, mempromosikan relaksasi alami serta mengatur dan menstabilkan emosi (Y. W. .…”
Section: Pendahuluanunclassified
“…7,8 Aromaterapi, akupresür, masaj, Emotional Freedom Tecniuqe (EFT)-Duygusal Özgürleşme Tekniği (DÖT), müzik terapi hemşireler tarafından ameliyat öncesi hastaların yaşadığı anksiyeteyi kontrol altına almada kullanılan etkili tamamlayıcı yöntemler olarak karşımıza çıkmaktadır. 3,4,[7][8][9][10][11][12][13] Bu yöntemler, günümüzde bireylerin sağlığının korunmasında ve geliştirilmesinde, hastalıkların önlenmesinde, hastalık varlığında tıbbi tedaviye destek olarak sağlık profesyonelleri tarafından kullanılmaktadır. 14 Hiçbir yan etkisi olmayan, ucuz, uygulama esnasında başka bir personelin desteğini veya pahalı ekipman kullanımını gerektirmeyen bir teknik olan tamamlayıcı uygulamalar, ameliyat öncesi dönemde hastaların yaşadığı yüksek anksiyete nedeniyle ortaya çıkan istenmeyen durumları azaltarak veya önleyerek hemşirelik bakımının kalitesini arttırmakta ve hasta sonuçları üzerine olumlu etkiler yaratmaktadır.…”
Section: Introductionunclassified